Prevalence of raised Alanine Amino transaminase (ALT) in pregnant mothers: A Cross-sectional Study - TabindaKhalid,RubabaAbidNaqvi,NisarAhmedMalik,HamnaSarwar, TabindaKhalid,RubabaAbidNaqvi,NisarAhmedMalik,HamnaSarwar (Journal of Rawalpindi Medical College, 2020)
Objective: To determine the prevalence of raised ALT, common causes, and associated fetomaternal morbidity in pregnant mothers presenting, at cantonment general hospital Rawalpindi Materials and Methods: This was a cross-sectional study conducted at cantonment general hospital Rawalpindi from July 2016 till June 2017. Results: Out of 1924 women, 102 were identified with raised ALT making a prevalence of 5.3%. Sixty-one (59.8%) were booked. The hypertensive group which included severe preeclampsia, chronic hypertension with superimposed preeclampsia/eclampsia were 55(53.9%), intrahepatic cholestasis of pregnancy(ICP) 32(31.7%), acute viral hepatitis 9(8.8%), Acute fatty liver of pregnancy(AFLP) 2(1.96%), and unknown cause in 4(3.92%). Mean ALT levels were 54.1±6.94, 71.28±23.25, 84.22±27.82, 231.5±47.37 respectively. In four cases no definitive cause could be identified with the available tests were labeled as an unknown group, having a mean ALT level of 79.25±10.07. (p=0.01). Term delivery occurred in 71(69.6%), while 31(30.39%) were preterm. There was one termination of pregnancy. Vaginal birth occurred in 42(42.2%), and 53(51.9%) underwent emergency cesarean. There was one peripartum hysterectomy. Meconium stain of liquor was 19(18.6%). The birth weight of most babies 73(71.5%) was between 2-3 kilograms only three were ≤ 1 kilograms. Eight cases of postpartum hemorrhage, three maternal deaths, and six perinatal/early neonatal deaths were observed. Conclusion: Raised ALT in pregnancy leads to increased fetomaternal complications. Severe preeclampsia and obstetric cholestasis were the commonest causes. Women of younger age groups were having acute viral hepatitis. Timely recognition and diagnosis are essential to institute appropriate management strategies.